Biology of leaf gall-inducing Thlibothrips manipurenis Muraleedharan, 1982 on Ardisia sp. (Myrsinaceae) in north-eastern India (Thysanoptera: Tubulifera: Phlaeothripidae). - Taptamani, Heishnam; Varatharajan, Rameiyer; Raman, Anantanarayanan (Contributions to Entomology = Beiträge zur Entomologie, 2012)
Biology of the epiphyllous roll-gall-inducing Thlibothrips manipurensis was studied on Ardisia sp. under laboratory conditions. T. manipurensis laid eggs linearly along the margins of tender leaves. Eggs hatched in 6.8 d and the larval duration was 3.4 and 8.2 d for larvae I and II, respectively. After 20.2 h as prepupa, T. manipurensis grew into pupa; adult emergence occurred in 4 d. Each female laid 34±7 eggs and the mean longevity of the adult was 10.2 d. Increase in thrips numbers correlated with the age of the gall: 15 individuals/gall occurred in young (4–10 d) galls, whereas 28 occurred in mature (20 d) galls, and 36 in old (25 d) galls. Male–female ratio in old galls was 1:5. Mature galls included a homogeneous tissue structure, made of 12–15 layers of parenchyma cells with no distinction into spongy and palisade cells. The gall-mesophyll cells adjacent to the upper and lower epidermises developed essentially through anticlinal divisions of the primordial cells, whereas those in mid regions developed through periclinal divisions; the latter facilitates the blade to roll inwards. Cells in the mid region of the galled lamina were larger than those occurring adjacent to the epidermises. Bulk of the cells in the mid-region of the galled lamina included darkly staining inclusions, which, in high likelihood, were phenolic materials. Thliobothrips is an ally of Gynaikothrips. Thlibothrips and Gynaikothrips are the better known gall-inducing taxa. The roll galls induced by Thlibothrips manipurensis on Ardisia sp. (Myrsinaceae, Asterids, Eudicots) are highly similar to those induced by Gynaikothrips flaviantennatus on the leaves of Casearia elliptica (Salicaceae: Samydeae, Rosids, Eudicots) in southern India. Because the Rosids and Asterids are considered related phylogenetically, the possible pathways taken by species of Gynaikothrips and Thlibothrips to radiate exploring different, but related plant taxa appear striking. Keywords Ardisia sp., galls, marginal-leaf rolls, Myrsinaceae, Phlaeothripidae, population patterns through development, Thlibothrips manipurensis, Thysanoptera, Tubulifera.